(untitled) (Bangladesh Oncology Journal, 2009)
This study was carried out in the Department of Oncology of Bangabandhu Sheikh Mujib Medical University from 1st January 2005 to 31st December 2005. A total number of 1107 cancer patients were included, of them 72% were smoker, 500 were male and 607 were female. So the male to female ratio was 1: 1.21. Highest incidence of malignancy was observed in the age of 46 to 60. Top five malignancies in female like- Breast, Cervix, Ovary, Gall Bladder, Stomach. Top five malignancies in male like- Lung, Stomach, Liver, Lymphoma, and Colon. (Bang. Onc. J. 2009; 4 (2) : 59-62)